The Influence of Teaching Methods, Learning Media, and School Facilities on Students' Learning Motivation - Dinda Jumiati; Hartono Hartono; Mirawati Mirawati (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
Learning motivation is a critical factor in vocational education, yet many students at SMK Negeri 2 Pekanbaru show suboptimal motivation levels, potentially linked to the quality of teaching methods, learning media, and school facilities. This study aims to analyze the influence of these three variables on students’ learning motivation at SMK Negeri 2 Pekanbaru. Using a correlational quantitative survey design with an ex post facto approach, the study involved 67 students from class X.2 selected through purposive sampling. Data were collected through a validated Likert-scale questionnaire (40 items) and analyzed using Pearson correlation and multiple linear regression. The results show that all three variables are significantly correlated with learning motivation: teaching methods (r = 0.319; p = 0.008), learning media (r = 0.463; p < 0.001), and school facilities (r = 0.411; p < 0.001). Simultaneously, the three variables significantly influence learning motivation (F = 7.150; p < 0.05), explaining 25.4% of its variance. Partially, only learning media exerts a significant influence (β = 0.333; p = 0.019). These findings highlight the importance of optimizing learning media as a primary strategy to enhance student motivation in vocational high school settings.